Predicting β-lactam susceptibility from the genome of Streptococcus pneumoniae and other mitis group streptococci - Eriksen, Helle Brander; Fuursted, Kurt; Jensen, Anders; Jensen, Christian Salgård; Nielsen, Xiaohui; Christensen, Jens Jørgen; Shewmaker, Patricia; Rebelo, Ana Rita; Aarestrup, Frank Møller; Schønning, Kristian; Slotved, Hans-Christian; , the One Day in Denmark (ODiD) Consortium (Frontiers in Microbiology, 2023)
Introduction For Streptococcus pneumoniae, β-lactam susceptibility can be predicted from the amino acid sequence of the penicillin-binding proteins PBP1a, PBP2b, and PBP2x. The combination of PBP-subtypes provides a PBP-profile, which correlates to a phenotypic minimal inhibitory concentration (MIC). The non-S. pneumoniae Mitis-group streptococci (MGS) have similar PBPs and exchange pbp-alleles with S. pneumoniae. We studied whether a simple BLAST analysis could be used to predict phenotypic susceptibility in Danish S. pneumoniae isolates and in internationally collected MGS. Method Isolates with available WGS and phenotypic susceptibility data were included. For each isolate, the best matching PBP-profile was identified by BLAST analysis. The corresponding MICs for penicillin and ceftriaxone was retrieved. Category agreement (CA), minor-, major-, and very major discrepancy was calculated. Genotypic-phenotypic accuracy was examined with Deming regression. Results Among 88 S. pneumoniae isolates, 55 isolates had a recognized PBP-profile, and CA was 100% for penicillin and 98.2% for ceftriaxone. In 33 S. pneumoniae isolates with a new PBP-profile, CA was 90.9% (penicillin) and 93.8% (ceftriaxone) using the nearest recognized PBP-profile. Applying the S. pneumoniae database to non-S. pneumoniae MGS revealed that none had a recognized PBP-profile. For Streptococcus pseudopneumoniae, CA was 100% for penicillin and ceftriaxone in 19 susceptible isolates. In 33 Streptococcus mitis isolates, CA was 75.8% (penicillin) and 86.2% (ceftriaxone) and in 25 Streptococcus oralis isolates CA was 8% (penicillin) and 100% (ceftriaxone). Conclusion Using a simple BLAST analysis, genotypic susceptibility prediction was accurate in Danish S. pneumoniae isolates, particularly in isolates with recognized PBP-profiles. Susceptibility was poorly predicted in other MGS using the current database.